Development and Validation of a Competency-Based Education Model Suitable for Undergraduate Human Nutrition and Dietetics Training in Uganda: A Modified Delphi Process - Kikomeko, Peterson Kato; Ochola, Sophie; Kaaya, Archileo N.; Ogada, Irene; Birungi, Tracy Lukiya; Nakitto, Peace (Research square, 2021)
Competency-based education (CBE) equips health professionals with the requisite competencies for health systems performance. This study aimed to develop and validate a CBE model suitable for teaching Human Nutrition/Human Nutrition and Dietetics (HN/HND) at the undergraduate level in Uganda.
Keywords: Competency-based education; Human Nutrition and Dietetics; Health Professionals Training; Undergraduate